Single-cell-array biomass-templated architecture of hierarchical porous electrocatalysts for Zn–air and Zn–H2O2 batteries. Issue 29 (22nd March 2023) - Zhu, Zhenjiang; Jin, Liangyu; Zhou, Meng; Fu, Kui; Meng, Fancheng; Wei, Xiangfeng; Liu, Jiehua
Abstract : Hierarchical macro–meso–microporous ZIF-67/nori-derived electrocatalysts were synthesized using single-cell-layered biomass, and yielded a maximum power density of 476 mW cm −2 in a Zn–H2 O2 battery. Abstract : Hierarchically macro–meso–microporous ZIF-67/nori-derived electrocatalysts were synthesized by using single-cell-array nori and ZIF-67 as macroporous and microporous templates, and KOH as a meso/micropore-forming reagent. The ZIF-67/nori-800-based Zn–H2 O2 battery achieved a high maximum power density, of 476 mW cm −2, and a specific energy density of 964 W h kg −1 at 50 mA cm −2 .